2005
DOI: 10.1634/theoncologist.10-4-262
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of Surgical Risk in Oncogeriatric Patients

Abstract: Cancer is a prevalent disease in our aging population; however, few oncologists are familiar with caring for oncogeriatric patients. Surgery is presently the treatment of choice for most solid tumors, but it is frequently delivered in a suboptimal way in this patient subsetting. Undertreatment is often justified with the concern of an unsustainable toxicity, while overtreatment can be related to the lack of knowledge in optimizing preoperative risk assessment. To draw new light on this issue, several surgeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(79 citation statements)
references
References 72 publications
1
75
0
3
Order By: Relevance
“…However, despite good overall calibration and discrimination on the whole cohort, all the risk stratification scores failed in predicting outcome on an individual basis. It has been recently suggested that, in order to achieve accurate individualized forecasts of operative risk in aged cancer patients, a single risk score is insufficient, and a sum of different scales and scores should be employed: the PACE (Preoperative Assessment of Cancer in the Elderly,) study [23], a prospective international study, with the aim at outlining the fitness of elderly surgical patients with malignancies, appeared to be able to define the correlation of some scores (ECOG Performance Status, Activities of Daily Living -ADL and Instrumental Activities of Daily Living -IADL) to short-term surgical outcome when applied to 215 elderly patients undergoing breast, colorectal, upper GI, and urogenital surgery for malignancy. However the number of patients receiving major surgery for gastroesophageal cancer was too small (nine patients) in this study to draw any meaningful conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite good overall calibration and discrimination on the whole cohort, all the risk stratification scores failed in predicting outcome on an individual basis. It has been recently suggested that, in order to achieve accurate individualized forecasts of operative risk in aged cancer patients, a single risk score is insufficient, and a sum of different scales and scores should be employed: the PACE (Preoperative Assessment of Cancer in the Elderly,) study [23], a prospective international study, with the aim at outlining the fitness of elderly surgical patients with malignancies, appeared to be able to define the correlation of some scores (ECOG Performance Status, Activities of Daily Living -ADL and Instrumental Activities of Daily Living -IADL) to short-term surgical outcome when applied to 215 elderly patients undergoing breast, colorectal, upper GI, and urogenital surgery for malignancy. However the number of patients receiving major surgery for gastroesophageal cancer was too small (nine patients) in this study to draw any meaningful conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…This will require more prospective studies involving aged patients since only few have been published so far [7,9,23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the need for assistance with IADLs appeared to predict postoperative complications in a series of older adults undergoing cancer-related surgery (P ϭ .043). 42 Similarly, in a series of patients with ovarian cancer receiving standard cytotoxic chemotherapy, the need for functional assistance (defined as living at home with assistance or living in an institution with medical assistance) was found to be predictive of severe treatment-related toxicity (P ϭ .048). 43 Observational data have indicated that pain severity in older adults with cancer is correlated directly with ADL and IADL disability.…”
Section: Functional Statusmentioning
confidence: 95%
“…Additional geriatric specific assessments may be required, including an assessment of overall functional status, nutrition and cognitive status [4]. Particularly in the oncogeriatric population, tools such as the Amercian Society of Anaesthesiologists (ASA) score and the Preoperative Assessment of Cancer in the Elderly (PACE) instrument may be invaluable [5]. A strong emphasis is also placed on intraoperative care which often require invasive cardiovascular monitoring, careful maintanence of core temperature and volume status.…”
Section: Discussionmentioning
confidence: 99%